Factors affecting the utilisation of voluntary counselling and testing (VCT) services for HIV/AIDS in Sowa, Botswana. - Akhiwu, Patrick (My University, 2012)
Introduction Voluntary Counselling and Testing (VCT) play a crucial role in the control and management of the HIV/AIDS epidemic. It is essential to understand the factors that influence the utilisation of VCT to improve implementation of measures that encourage VCT uptake. The purpose of this study was to determine factors affecting the utilisation of Voluntary Counselling and Testing (VCT) services for HIV/AIDS in Sowa, Botswana. Methodology A cross-sectional study was carried out by collecting data from 71 randomly selected participants residing in the community of Sowa, Botswana. Open and close ended questions were used. Relevant demographic data were collected from each respondent. Univariate and multivariate analysis was done using chi square test and logistic regression models through STATA11 statistical software. Results About half of the respondents were willing to utilise the VCT services. Willingness to utilise VCT was significantly associated with the respondents' choice of VCT centres, worry about confidentiality at VCT centres, and concern about their partners' being aware of their use of VCT. The expected reactions of their partner, family and community to the use of VCT by the respondents, in addition to the willingness of respondents to inform their partners the result of their HIV test, were other factors associated with the use of VCT. Multivariate regression showed that being "not worried" (AOR 33.48; 95CI 5.63 - 199.15) about confidentiality at VCT centres predicted the willingness to use VCT. In addition, not worried that their partners were aware they had utilised VCT (AOR 7.25; 95CI 1.69- 31.14), and readiness to inform their partners about the result of their HIV test (AOR 14.96; 95CI 3.74- 59.85), predicted the willingness of respondents to utilise VCT. Similarly, the expectation of a happy reaction from partner (AOR 47.02; 95CI 3.83- 577.11) and family (AOR 45.13 95CI 3.28-620.72) on being aware the respondent had used VCT, also predicted willingness to use VCT. Conclusion This study confirmed that stigma related to VCT use and confidentiality at VCT centres influence the utilisation of VCT services. Also, concern about partner's awareness that a respondent had used VCT and the expected response of partner, family, and community, were all important influencing factors to the utilisation of voluntary counseling and HIV testing services. These issues need to be addressed in order to increase VCT uptake among individuals and the community.
Keywords: HIV/AIDS counselling Botswana; HIV-1--diagnosis; Acquired Immunodeficiency Syndrome--diagnosis